2016
DOI: 10.1007/s00167-016-4232-9
|View full text |Cite
|
Sign up to set email alerts
|

Progression of medial compartmental osteoarthritis 2–8 years after lateral closing-wedge high tibial osteotomy

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 56 publications
0
19
1
Order By: Relevance
“…In the present study, no joint space narrowing or increase in space was observed in 73% of knees, and 57% of all knees increased their minimal JSW by more than 0.5 mm. The difference with respect to our data was the small proportion of patients with a decreasing minimal JSW after HTO (27% in the current study’s knees vs 48% 13 ) (Table 2).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…In the present study, no joint space narrowing or increase in space was observed in 73% of knees, and 57% of all knees increased their minimal JSW by more than 0.5 mm. The difference with respect to our data was the small proportion of patients with a decreasing minimal JSW after HTO (27% in the current study’s knees vs 48% 13 ) (Table 2).…”
Section: Discussioncontrasting
confidence: 87%
“…Previous studies showed similar widening of the medial joint space, ranging from 0.4 mm to 1.1 mm, but did not report the serial change in the minimal JSW or the endurance of healed cartilage. 30,37 Huizinga et al 13 reported that the minimal JSW changed from 3.4 ± 1.5 mm preoperatively to 3.3 ± 1.6 mm at an average follow-up of 5.2 years. No joint space narrowing or increase in space was observed in 52% of patients, and 31% of all patients increased their minimal JSW by more than 0.5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of this study was that it might be considered short-term relative to previous studies examining this patient population. [36][37][38] The planned analysis of the 24-month data will provide further knowledge regarding the safety and efficacy of this implant. Future studies will also require greater sample sizes to obtain more accurate and precise estimates of the intervention's effect.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologic outcomes were measured with Kellgren‐Lawrence (K‐L) grade , joint space width of medial and lateral compartment , and hip‐knee‐ankle (HKA) angle using simple radiograph. MRI was evaluated before injection and 3 and 6 months after injection.…”
Section: Methodsmentioning
confidence: 99%